2014
DOI: 10.1371/journal.pone.0113171
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Trans-Seasonal Variability in Water Column Biomass for a Highly Migratory, Deep Diving Predator

Abstract: The deployment of animal-borne electronic tags is revolutionizing our understanding of how pelagic species respond to their environment by providing in situ oceanographic information such as temperature, salinity, and light measurements. These tags, deployed on pelagic animals, provide data that can be used to study the ecological context of their foraging behaviour and surrounding environment. Satellite-derived measures of ocean colour reveal temporal and spatial variability of surface chlorophyll-a (a useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…Random intercept models were then compared with random slope models (a random slope for PDI was added to the random slope models). Both seal and latitude were included as random terms in our analysis to allow for potential tag measurement variability and likely effect on phytoplankton abundance in the water column respectively (for details see O'Toole et al, 2014b). Second, we assessed the effect of inclusion of an autocorrelation term in the resulting optimal model by using the AR-1 autocorrelation (corAR1) argument.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Random intercept models were then compared with random slope models (a random slope for PDI was added to the random slope models). Both seal and latitude were included as random terms in our analysis to allow for potential tag measurement variability and likely effect on phytoplankton abundance in the water column respectively (for details see O'Toole et al, 2014b). Second, we assessed the effect of inclusion of an autocorrelation term in the resulting optimal model by using the AR-1 autocorrelation (corAR1) argument.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplankton is consequently the main cause of light attenuation if it is assumed colored dissolved organic matter (CDOM) and detritus degradation products covary with phytoplankton (Bricaud et al, 1981) and physical properties are constant (Bricaud et al, 1998). Light data collected during daylight hours by marine animals can therefore provide a useful index for plankton density concurrent with animal movement (Teo et al, 2009;Guinet et al, 2013;O'Toole et al, 2014b) and have revealed seasonal trends typical of Southern Ocean productivity south of Iles Kerguelen and Macquarie Island (Jaud et al, 2012;O'Toole et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…As prey density per se is not known to be influenced by water transparency, this metric provides strong support for the influential role of oceanographic features. Further, shading of the water column from the presence of phytoplankton and zooplankton can directly affect water transparency 47,72,73 . Mesopelagic prey are also likely more abundant in shallower waters when there is higher productivity (i.e.…”
Section: Seals Reveal the Distribution And Abundance Of Mesopelagic Pmentioning
confidence: 99%
“…A prime example is the improved knowledge of how elephant seals use specific water masses and oceanographic features obtained from high-quality temperature-salinity profiles collected onboard tags (e.g., Biuw et al, 2007;Labrousse et al, 2015;Hindell et al, 2016). Other novel approaches include the usage of onboard light-levels to infer bio-optical properties of the water column, including phytoplankton concentrations (Jaud et al, 2012;O'Toole et al, 2014), as well as direct fluorometry measurements to evaluate productivity influences on animal foraging. These clearly demonstrate the benefits gained from collecting environmental information onboard the same tag that is collecting the behavioral (dive) information.…”
Section: Perspectives and Emergent Areasmentioning
confidence: 99%